2019
DOI: 10.3390/app9122552
|View full text |Cite
|
Sign up to set email alerts
|

Pistacia Atlantica Desf., a Source of Healthy Vegetable Oil

Abstract: Pistacia atlantica, which belongs to the Anacardiaceae family, is an important species for rural people in arid and semi-arid areas. The fruit, rich in oil, is used in traditional medicine for the treatment of various diseases. The oil extracted from this species growing in a northern area of Algeria and its fatty acid composition were previously studied. However, the largest areas where this species is present (traditional cultivation) is located in southern Algeria. Moreover, studies on oil fatty acid compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…For MUFA intakes, international recommendations vary greatly between 12-25%. Moreover, the ratio of linoleic to linolenic must be lesser than five (Kalonji et al, 2012;Ristić-Medić et al, 2013;Labdelli et al, 2019). Our results showed, at 24 DAF, the chia seeds fulfill the recommendations mentioned above (Tab.…”
Section: Fatty Acid Compositionsupporting
confidence: 66%
See 1 more Smart Citation
“…For MUFA intakes, international recommendations vary greatly between 12-25%. Moreover, the ratio of linoleic to linolenic must be lesser than five (Kalonji et al, 2012;Ristić-Medić et al, 2013;Labdelli et al, 2019). Our results showed, at 24 DAF, the chia seeds fulfill the recommendations mentioned above (Tab.…”
Section: Fatty Acid Compositionsupporting
confidence: 66%
“…These values are significantly higher than those of most vegetable oils, e.g. canola oil (0.36), olive oil (0.08-0.12), soybean oil (0.15), Safflower (0.01) Atlas pistachio (0.10) and walnut oil (0.25) (Galão et al, 2014;Ojeda-Amador et al, 2018;Rodrigues et al, 2018;Beyzi et al, 2019;Labdelli et al, 2019;Roche et al, 2019). The tocopherol content increased in same way between 17 to 24 DAF (Tab.…”
Section: Fatty Acid Compositionmentioning
confidence: 82%
“…The importance of functional foods, nutraceuticals, food supplements and other natural diet compounds has been associated with health promotion and disease prevention. Fatty acids (FAs) have important biological functions, such as being components of biological membranes, precursors of different molecules, energy storage and the transport of vitamins [1,2]. Lipids, carbohydrates, proteins, minerals and vitamins present in all foods are essential nutrients, compounds that cannot be synthetized by the human body in adequate quantities and must be supplied by the diet [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Other applications have been reported such as the use of their galls as a raw material for tanning in the leather industry, [3] insect repellent, and fumigant against plant fungi diseases. [4] In recent decades, those properties are supported and confirmed by multiple research, whither diverse phytochemical groups were identified and revealed from P. atlantica Desf. such as terpenoids (essential oils), [5] phenolic compounds, [6,7] flavonoids, [8] fatty acids and sterols.…”
Section: Introductionmentioning
confidence: 78%